Effect of Er: YAG laser on the bond strength of glass ceramic to bleached enamel and mechanism investigation - Jingwen Miao; Jing Ye; Junjie Wu; JiaHao Qin; Ben Ma; Jian Zhang; Ying Liu (BMC Oral Health, 2026)
Abstract Background This study aimed to evaluate the efficacy of Er: YAG laser treatment for glass-ceramic bonding to bleached enamel and to further investigate the potential mechanisms. Methods This in vitro study included 132 molars, with each molar used to prepare a single specimen. A total of 48 enamel slices, 48 enamel blocks, and 36 embedded whole-tooth specimens were prepared. The specimens were randomly allocated to four groups: the Control group, hydrogen peroxide (HP) group, HP combined with sodium ascorbate (HP-SA) group, and HP combined with Er: YAG laser (HP-Er: YAG) group. They were subsequently evaluated for enamel surface morphology, residual hydrogen peroxide (H 2 O 2 ) concentration, resin degree of conversion (DC), resin penetration, shear bond strength (SBS), and failure mode. Results SEM showed that the HP-Er: YAG group exhibited rough and irregular enamel surfaces, while the HP and HP-SA groups showed no obvious morphological changes. Compared with the HP group (109.60 ± 10.38 µmol/L), H 2 O 2 concentrations were significantly lower in the HP-SA (51.05 ± 20.06 µmol/L) and HP-Er: YAG (29.96 ± 13.01 µmol/L) groups ( P < 0.0001). The HP-Er: YAG group showed a lower concentration than the HP-SA group ( P < 0.05).The DC of the HP-Er: YAG group (51.10 ± 7.02%) was comparable to that of the Control (59.84 ± 5.36%) and HP-SA (41.82 ± 7.28%) groups ( P > 0.05). The Control and HP-Er: YAG groups exhibited extensive resin penetration at the enamel-adhesive interface. SBS was significantly higher in the Control (21.92 ± 4.33 MPa) and HP-Er: YAG (22.62 ± 4.06 MPa) groups than in the HP (13.46 ± 3.62 MPa) and HP-SA (17.76 ± 2.56 MPa) groups ( P < 0.01). For ARI scores, the Control and HP-Er: YAG groups did not differ significantly ( P > 0.05), whereas all other pairwise comparisons were statistically significant ( P < 0.05). Conclusion Reduced H 2 O 2 levels, increased resin polymerization, and modification of the enamel surface may contribute to the improved bonding performance observed after Er: YAG laser treatment of bleached enamel. Compared with 10% SA treatment for 10 min, Er: YAG laser was more effective in restoring bond strength, suggesting its potential for immediate glass‑ceramic bonding to bleached enamel.